Tantangan Lembaga Pendidikan Di Jepang Dalam Menyambut Era Society 5.0 - Ayyub, Ichlasul (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2023)
Era Society 5.0 or called Society 5.0 was first echoed by the Japanese government. This era is an era where drastic changes occur in the industrial world and social structure. Many things need to be prepared, one of which is preparing human resources capable of adapting to that era, the things that can be done for this is through education. Era Society 5.0 requires someone to be able to integrate their activities with digital technology. This article examines what challenges will be faced by educational institutions in Japan and what must be done to be able to form the human resources needed by the world of work in Japan in the era of Society 5.0. This research has the objective of describing what are the challenges of educational institutions in Japan to graduate human resources who are ready to compete in the era of society 5.0 and how to solve them. This research uses a qualitative research approach. The data collection technique was carried out by collecting literature data. This study collects information or data from various sources such as articles that are relevant to the issue of Education in Japan’s Society 5.0 era. To face the era of Society 5.0, the world of education in Japan has carried out various corrective actions, including reforming education in the form of a lecture system and lecture materials, providing facilities for students and alumni to be able to discuss with companies in Japan, and establishing collaborations with foreign universities in the form of providing double degree programs.